Вплив тиристорного перетворювача на пульсації електромагнітного моменту асинхронного двигуна при параметричному управлінні - Лобов, В.Й.; Лобова, К.В. (Електротехніка і електромеханіка, 2017)
Представлені розрахунки та фізичне моделювання коливальних складових електромагнітного моменту при зміні параметрів асинхронного електродвигуна, елементів силових схем перетворювачів, побудованих на резисторнотиристорних модулях. Установлено, що величина пульсацій електромагнітного моменту у квазісталих режимах залежить від вибраної силової схеми статорного і роторного комутаторів перетворювача, складу елементів, що входять до них, і схеми їх з’єднання, зміни величини кутів відкриття вентилями, способи їх управління, частота обертання ротора, параметри механізму – моменти статичний та інерції. Запропоновано використовувати для дослідження узагальнену схему параметричного управління асинхронного електродвигуна. Представлены расчеты и физическое моделирование колебательных составляющих электромагнитного момента при изменении параметров асинхронного электродвигателя, элементов силовых схем преобразователей, построенных на резисторно-тиристорных модулях. Установлено, что величина пульсаций электромагнитного момента в квазипостоянных режимах зависит от выбранной силовой схемы статорной и роторной коммутаторов преобразователя, состава элементов, входящих в них, и схемы их соединения, изменения величины углов открытия вентилями, способы их управления, частота вращения ротора, параметры механизма - моменты статический и инерции. Предложено использовать для исследования обобщенную схему параметрического управления асинхронного электродвигателя. Purpose. The purpose of the work is to identify the parameters influence of the electric motor, the power circuits elements of the converters, built on resistor-thyristor modules, the static torque and the moment of inertia of the mechanism on the vibrational components of the induction motor’s electromagnetic moment. Methodology. The methodological basis for the solution of the task is an integrated approach. The application of the generalized control circuit for an induction electric motor and its mathematical description made it possible to analyze various power circuits of parametric control of an induction electric motor. To create a common control algorithm, effectively use the computer for calculations. To perform qualitative and quantitative analysis of the amplitudes and frequencies of the vibrational components of the electromagnetic torque of the electric motor. Results. The conducted researches allowed to reveal the peculiarities of the effect of the parameters of the elements of various types of power circuits of the parametric control converters on the vibrational components of the electromagnetic torque of an induction electric motor. Calculations and physical modeling have been performed, it has been possible to establish the conditions for the occurrence of electromagnetic pulsations and to determine the ways of their elimination. It was found that the magnitude of pulsations of the electromagnetic moment of an induction electric motor in quasi-permanent modes depends on the selected power circuit of the converter's stator and rotor commutators, the composition of the elements included in them, and the connection circuits. Comparison of calculated and experimental waveform when starting induction electric motors indicates that the pulsation of the electromagnetic torque is affected by: the size of the opening angle of the valves, their control methods, the rotor speed, the parameters of the electric motor and the mechanism are static and inertial moments. At the same time, it was revealed that the use of resistor-thyristor modules in the power circuits of the stator and rotary commutators reduces the magnitude of the pulsation of the electromagnetic torque of the induction electric motor. Increase the value of its maximum and average torques. Limit the magnitude of the shock and alternating torques when it starts and the transition from one speed to another. Scientific novelty. It is proposed to use a generalized circuit of parametric control of an induction electric motor for studying the change in the electromagnetic torque. The circuit consists of resistor – thyristor modules in stator and rotary commutators. The presented technique allowed simultaneously to investigate transients during the control of an induction electric motor by various power circuits of converters. The results of calculations allow choosing the necessary power circuit, taking into account the vibrational components of the electromagnetic torque of the induction motor.